2002
DOI: 10.1021/ja026377h
|View full text |Cite
|
Sign up to set email alerts
|

Routes to Metallodendrimers of the [Re6(μ3-Se)8]2+ Core-Containing Clusters

Abstract: The reaction of [Re6(mu3-Se)8(PEt3)5(MeCN)](SbF6)2 with an excess of 1,2-bis(4-pyridyl)ethane (L1) and (E)-1,2-bis(4-pyridyl)ethene (L2) produced [Re6(mu3-Se)8(PEt3)5(L1)](SbF6)2 and [Re6(mu3-Se)8(PEt3)5(L2)](SbF6)2, respectively, each bearing an accessible pyridyl N atom capable of further metal coordination. Reacting these cluster complex-based ligands with [Re6(mu3-Se)8(MeCN)6](SbF6)2 afforded two heptacluster metallodendrimers, each featuring a central [Re6(mu3-Se)8]2+ cluster core surrounded by six units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Dyad 1 was prepared by reacting stoichiometric amounts of 2 and 3 (Scheme ). For this kind of ligand substitution, long reaction times and rather high temperatures are usually required 12. Therefore, a suspension of 2 and 3 in dry chlorobenzene was refluxed under argon for five days, resulting in the formation of a brown precipitate, which then was washed with toluene and chloroform to remove traces of unreacted starting materials.…”
Section: Resultsmentioning
confidence: 99%
“…Dyad 1 was prepared by reacting stoichiometric amounts of 2 and 3 (Scheme ). For this kind of ligand substitution, long reaction times and rather high temperatures are usually required 12. Therefore, a suspension of 2 and 3 in dry chlorobenzene was refluxed under argon for five days, resulting in the formation of a brown precipitate, which then was washed with toluene and chloroform to remove traces of unreacted starting materials.…”
Section: Resultsmentioning
confidence: 99%
“…1-5,8,16 -19 The substitutional lability of the apical halide ligands make these molecular clusters a reasonable point of departure for constructing multicluster aggregates, thus contributing to the active area of supramolecular inorganic chemistry. 3,5,11,[19][20][21][22][23][24] In addition, the 24e Re 6 Q 8 X 6 4Ϫ cluster exhibit a singlet ground state and are diamagnetic, 30,37,38,48,49 some of its phospine-substituted analogues are clearly diamagnetic by 31 P nuclear magnetic resonance ͑NMR͒. 3,21 Whereas, the 23e Re 6 S 8 X 6 3Ϫ and the Re 6 Se 8 I 6 3Ϫ cluster ions are clearly paramagnetic, and, each one characterized by a SOMO spanning the ␥6 ϩ symmetry corresponding to a Kramers doublet as the ground state, as supported by the available EPR data.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,10,12,13,16,17,19,21,29 Moreover, the synthetic versatility of the ͓Re 6 Q 8 ͔ 2ϩ cluster core has allowed the synthesis of extended new porous materials that can be used as molecular sieves, or used as starting material for designing versatile chemical sensors for the detection of a large variety of vola-tile pollutants, 6,14,18,23 and it has been used as building blocks for constructing extended multicluster aggregates and exotic metallodendrimers. 2,3,11,20,24 The solution chemistry of the 24e clusters is well developed, but the chemistry of the 23e cluster is less known at present. 7,21 About a decade ago it was reported that the treatment of yellow acetonitrile solutions of the Re 6 Q 8 X 6 4Ϫ clusters with anhydrous acid induces an immediate color change to red owing to the formation of the hexarhenium protonated clusters Re 6 Q 7 (QH͒X 6 3Ϫ .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Thereadily tunable peripheral groups facilitate the rigid POSS as building blocks for the formation of high-ordered structures driven by intermolecular interactions such as hydrogen bonding [11] and metal coordination [12] to assemble coordination polymers.Recently, by coordination of thiol À POSS ligand with Cu I complex, anovel structure-defined 3D complex containing tetranuclear copper(I) cluster as secondary building unit has been demonstrated, [12b] indicating that the thiolÀPOSS is aversatile candidate in the design of metal cluster compounds.Inspired by this,w ec onsider that the thiol-POSS can be used as protecting shell ligands to induce the formation of new silver(I)-POSS cluster compounds, [13,14] which have never been reported. [7][8][9][10] Thereadily tunable peripheral groups facilitate the rigid POSS as building blocks for the formation of high-ordered structures driven by intermolecular interactions such as hydrogen bonding [11] and metal coordination [12] to assemble coordination polymers.Recently, by coordination of thiol À POSS ligand with Cu I complex, anovel structure-defined 3D complex containing tetranuclear copper(I) cluster as secondary building unit has been demonstrated, [12b] indicating that the thiolÀPOSS is aversatile candidate in the design of metal cluster compounds.Inspired by this,w ec onsider that the thiol-POSS can be used as protecting shell ligands to induce the formation of new silver(I)-POSS cluster compounds, [13,14] which have never been reported.…”
Section: Silver(i) Nanoclusters Have Attracted Much Attention Inmentioning
confidence: 99%